Differential localization of tropomyosin isoforms in cultured nonmuscle cells (The Rockefeller University Press, 1988)
We have previously shown that chicken embryo fibroblast (CEF) cells and human bladder carcinoma (EJ) cells contain multiple isoforms of tropomyosin, identified as a, b, 1, 2, and 3 in CEF cells and 1, 2, 3, 4, and 5 in human EJ cells by one-dimensional SDS-PAGE (Lin, J. J.-C., D. M. Helfman, S. H. Hughes, and C.-S. Chou. 1985. J. Cell Biol. 100: 692-703; and Lin, J. J.-C., S. Yamashiro-Matsumura, and F. Matsumura. 1984. Cancer Cells 1:57-65). Both isoform 3 (TM-3) of CEF and isoforms 4,5 (TM-4,-5) of human EJ cells are the minor isoforms found respectively in normal chicken and human cells. They have a lower apparent molecular mass and show a weaker affinity to actin filaments when compared to the higher molecular mass isoforms. Using individual tropomyosin isoforms immobilized on nitrocellulose papers and sequential absorption of polyclonal antiserum on these papers, we have prepared antibodies specific to CEF TM-3 and to CEF TM-1,-2. In addition, two of our antitropomyosin mAbs, CG beta 6 and CG3, have now been demonstrated by Western blots, immunoprecipitation, and two- dimensional gel analysis to have specificities to human EJ TM-3 and TM- 5, respectively. By using these isoform-specific reagents, we are able to compare the intracellular localizations of the lower and higher molecular mass isoforms in both CEF and human EJ cells. We have found that both lower and higher molecular mass isoforms of tropomyosin are localized along stress fibers of cells, as one would expect. However, the lower molecular mass isoforms are also distributed in regions near ruffling membranes. Further evidence for this different localization of different tropomyosin isoforms comes from double-label immunofluorescence microscopy on the same CEF cells with affinity- purified antibody against TM-3, and monoclonal CG beta 6 antibody against TM-a, -b, -1, and -2 of CEF tropomyosin. The presence of the lower molecular mass isoform of tropomyosin in ruffling membranes may indicate a novel way for the nonmuscle cell to control the stability and organization of microfilaments, and to regulate the cell motility.